Primary treatment of water stored in rustic ponds through the application of chemical and biological coagulants: Tratamiento de aguas en estanques rústicos - Moreno-Cabrera, Gemma Arintzy; Alvarez-Arteaga, Gustavo; Orozco-Hernández, María Estela; Reyes-Zuazo, María Antonieta (Ecosistemas y Recursos Agropecuarios, 2021)
The study evaluated the coagulant effect of Moringa oleifera seed extract alone or in combination with aluminium sulphate for the treatmentof stored water in a rustic pond. Four treatments were tested from the individual and combined use of the extract with aluminium sulphate at60, 120 and 180 minutes of sedimentation. The combined treatments had removals greater than 95% of turbidity in the first 60 minutes, while the application of Moringa oleifera at 100% had a maximum removal of 90% up to 180 minutes. In the aluminium sulphate treatments there was a decrease in the pH in the water. The combination of Moringa oleifera seed extract and aluminium sulphate in a 70/30 w / w ratio presented the highest removal efficiency and sedimentation time, with the advantage of reducing costs and sediments with aluminium.